RELIGION, BELIEF, GENDER MAINSTREAMING, AND THETHEORY OF SOCIAL CONSTRUCTION - Sanuri, Sanuri (Jurnal Studi Gender Indonesia, 2012)
The topic of discussion in this article highlights gender mainstreaming as one of the contemporaryissues as an application of Social Construction theory which is formulated by Peter I. Berger andThomas Luckman. This theory describes a process where, through action and interaction, peopleare constantly creating a shared reality which is experienced as objectively factual and subjectivelymeaninffid. Social reality isconstructed in each of their respective societies in the sense that comes from the different standardsof truth, reality, and rationality among the communities. Reinterpretation of mainstream ofunderstanding gender is really as a creative product or a constructive behavior of individuals orgroups who then are able to influence the perspective of social life. Because of such a naturalflexibility of the gender mainstreaming, it needs to be juxtaposed with the kind of socialconstruction theory to see the extent of mutual influence between individuals and groups in societyand historical circumstances to produce a constructive value. This paper will also presents some ofthe intenaiths and culturals leading figures and thinkers who create varioust aspects of gendermainstreaming; theological, historical, biological, and anthropological meaning of the gendermainstreaming.Keywords: gender, sex, patriarchy, social construction.